The Marichev-Saigo-Maeda Fractional Calculus Operators Pertaining to the V-Function - S. Chandak; Biniyam Shimelis; Nigussie Abeye; A. Padma (Abstract and Applied Analysis)
In the present paper, we establish some composition formulas for Marichev-Saigo-Maeda (MSM) fractional calculus operators with V-function as the kernel. In addition, on account of V-function, a variety of known results associated with special functions such as the Mittag-Leffler function, exponential function, Struve’s function, Lommel’s function, the Bessel function, Wright’s generalized Bessel function, and the generalized hypergeometric function have been discovered by defining suitable values for the parameters.